Segmental Duplications: A Possible Mechanism of Hominid Uplift through MicroRNA Diversification - Maria A. Endriga; Aldrich Ivan Lois D. Burog; Denise Lauren V. Dalmacion; Custer C. Deocaris (Journal of Tropical Life Science, 2010)
MicroRNAs (miRNA) are 21 nucleotide-long gene silencers. Segmental duplications (SD) are among the driving forces in acquiring new genes. Both miRNA and SD are believed to have played a significant role in evolution, particularly in the divergence of humans (Homo sapiens) from the chimpanzee (Pan troglodytes). This study determines the distribution of miRNAs in humans and in chimpanzees, and presents a hypothesis on its significance in the occurrence of segmental duplications. MiRNA sequences from miRBASE were subjected to BLAT and BLAST to determine if miRNAs are located in SD regions or not. Homology between miRNAs was determined with ClustalW. BLAST was then used to determine whether the non-homologous human miRNA are homologous to any other part of the chimpanzee genome. We found that all 695 human miRNAs are found exclusively in SD regions, and that 67 are de novo miRNAs. Thirteen are homologues of chimpanzee miRNA, and 11 were possibly derived from non-miRNA regions in chimp. Of these, 6 were located in SD regions of the chimpanzee genome. Results indicate that miRNA evolution occurs within regions of segmental duplication and suggest that the presence of miRNA duplicates allows more exposure to mutations that could necessitate diversification, and possibly evolution, through sub- and neofunctionalization.Keywords: